Design and Simulation of a Thermal Heating Unit for a Room Heater. - Wabwire, Jovent Apollo (Kabale University, 2024)
This study focuses on designing and simulating a thermal heating unit, specifically a radiator, for use in room heating systems. The primary goal is to create an efficient and cost-effective solution that ensures thermal comfort in cold residential environments, even with outdoor temperatures as low as 15 °C, while keeping ventilation and exfiltration losses below 7065 ACH. The research involves a thorough literature review, design conceptualization, and an in-depth evaluation of various heating mechanisms. Critical design aspects, including heat transfer efficiency, material selection, and energy consumption, are carefully examined. The study also simulates the proposed heating unit, analyzing internal pressure, radiative surface temperature, and fluid turbulence of the working fluid. Simulation results confirm the unit's feasibility and effectiveness, showcasing its potential to improve energy efficiency and indoor comfort. This research contributes to the development of sustainable heating technologies and offers valuable guidance for future innovations in the field.